1996
DOI: 10.1046/j.1365-3024.1996.d01-19.x
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Cellular Immune Responses in Neonates From Cameroon

Abstract: T cell responses to leucoagglutinin, PPD, and seven Plasmodium falciparum blood stages antigens were investigated in 164 cord blood samples from Cameroonian neonates. In vitro T cell responses were measured by lymphocyte proliferation, and IL-2, IFN-gamma, and IL-4 release in the presence of crude schizont extract, purified Pf155/RESA protein, and synthetic peptides from Pf155/ RESA. Following culture in presence of leucoagglutinin or PPD, proliferation and cytokine production were very low, as compared to adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 21 publications
4
56
0
Order By: Relevance
“…IgM Abs reactive with a large number of blood stage Ags including the vaccine candidate MSP-1 (20 -22), are present in up to 25% of cord samples in sub-Saharan Africa. Plasmodial Ag-specific Th2-type responses have been recalled in cord blood mononuclear cell (CBMC) cultures (23).…”
Section: P Lasmodium Falciparum (Pf)mentioning
confidence: 99%
“…IgM Abs reactive with a large number of blood stage Ags including the vaccine candidate MSP-1 (20 -22), are present in up to 25% of cord samples in sub-Saharan Africa. Plasmodial Ag-specific Th2-type responses have been recalled in cord blood mononuclear cell (CBMC) cultures (23).…”
Section: P Lasmodium Falciparum (Pf)mentioning
confidence: 99%
“…The presence of IgM or IgE Abs to malaria Ags in cord blood constitutes prima facie evidence of in utero sensitization since, unlike IgG, these Ig isotypes do not cross the placenta from the maternal circulation (8,11,12). There have been relatively fewer studies of cord blood T cell responses to malaria Ags (12)(13)(14) and to our knowledge, no descriptions of cord blood B cell responses. These investigations, which reported lymphocyte proliferation, IL-2, IL-4, and IFN-␥ responses to lysates of infected red cells (i.e., schizont extracts), recombinant proteins, or synthetic antigenic peptides, suggest that a small proportion of infants become sensitized to malaria Ags during gestation.…”
Section: P Regnancy Is Associated With An Increased Risk Of Maternalmentioning
confidence: 99%
“…These investigations, which reported lymphocyte proliferation, IL-2, IL-4, and IFN-␥ responses to lysates of infected red cells (i.e., schizont extracts), recombinant proteins, or synthetic antigenic peptides, suggest that a small proportion of infants become sensitized to malaria Ags during gestation. For example, Fievet et al (14) reported that 9.8% of 164 Cameroonian newborns had cord blood lymphocyte (CBL) 3 IFN-␥ responses to native P. falciparum ring-infected erythrocyte surface Ag (Pf155/RESA).…”
Section: P Regnancy Is Associated With An Increased Risk Of Maternalmentioning
confidence: 99%
“…These have demonstrated low level reactivity to schizont extract, and certain blood stage Ag, and lack of reactivity to liver stage Ag [7][8][9][10][11]. Healthy adults living in malaria endemic regions generally have low level cellular reactivity to P. falciparum Ag despite lifelong exposure to parasites [12][13][14].…”
Section: Introductionmentioning
confidence: 99%